Penerapan Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Keaktifan dan Hasil Belajar IPA pada Siswa di MI Negeri 1 Yogyakarta - Yuliati, Erni (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to improve student activeness and learning outcomes through the application of the STAD type cooperative learning model. This type of research is classroom action research (PTK) which uses Robert Slavin's research model. This research was carried out in 2 cycles including planning, implementation, observation, and reflection stages. Data collection using instruments in the form of: student learning activity instruments, student attitudes and skills, teacher performance assessment instruments and tests. Data analysis techniques use qualitative analysis techniques and quantitative analysis. The results showed that the application of the STAD type cooperative learning model can increase student learning activities, having an impact on improving student learning outcomes. This can be seen from the average percentage of student activity in cycle I of 72.85%, cycle II of 86.42%. Meanwhile, the average student learning outcomes in the attitude aspect in cycle I was 80.74% and cycle II was 83.92%.